(3JLGQH GdGee hYhGbH Gdgees - (3CMeO Hf eMeO Hf jYbhH perSncnhrjg, CHh Ydj,J (B421 (3g` s
(3ChdgG (B:s
(3hONdJ SfI GMOi heGjI hajgG hdi jRjO Hf YHO Gdedc GdNdGaI hcfjJg GHh NGdO hgh GHf JSY hYTQjf SfI s
(3BNQgG (B:s
(3aeG eYfi CNPfG GdNQGL dSfg de JfJgi GSJhai GdGejQ NQGLgG efG ai GdVMi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B168s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B344s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQVhjI eTgO (B(4090) s
Keywords: (3GdJGQjNs